Factors Influencing the Entrepreneurial Behaviour of Agripreneurs in Andhra Pradesh - Deepthi, V; Rambabu, P; Gopikrishna, T (Journal of Agricultural Extension Management, 2018)
This study aims to identify the factors that influence the entrepreneurial behaviour of agripreneurs in three selected districts of Andhra Pradesh i.e. Chittoor, Krishna and Visakhapatnam, which were selected based on the highest number of agri linked enterprises. Two hundred and forty agripreneurs were selected through proportionate random sampling. Ex post- facto research design was used in the study. An attempt has been made to evolve a set of factors influencing the entrepreneurial behaviour through a data reduction process of factor analysis. The factors include: need for independence, communication network, innovativeness, achievement motivation, leadership behaviour, entrepreneurial self-efficacy, decision making and business skills. Results reveal that two factors such as entrepreneurial potential and entrepreneurial skill factor accounted for the maximum percentage of the total variance on overall entrepreneurial behaviour of agripreneurs.